Program for Determining the Dosimetric Contribution of Tc-99m Biokinetics in Estimating the Dose to the Heart of a Male Adult - Morales-Nizama, Rosa Adela (2023)
Purpose: To calculate the contribution of absorbed dose by organs in the biokinetics of Tc-99m when used for radiodiagnosis of the adult male heart employing a Matlab program. Methods: The absorbed self-dose of the adult male heart and absorbed dose by organs in the biokinetics of the heart when administering Tc-99m are estimated using the MIRD formalism and the Cristy-Eckerman representation, which have been employed to develop the algorithm in Matlab. Results: The results indicate that electron capture emissions of 1.446 (mGy/MBq) and Auger electrons of 0.062 (mGy/MBq) are entirely directed towards the target organ (heart) and contribute 29.33% and 1.25% respectively to its total dose. Additionally, the dosimetric contributions of biokinetic organs correspond to characteristic radiation emissions and gamma photons at 2.578 (mGy/MBq) for Tc-99m, representing 52.29% of its total dose. Conclusion: These dosimetric contributions are significant in estimating the total absorbed dose by the heart in adult males and should not be disregarded.